Islam in English (American Journal of Islam and Society, 2019)
The Quranic revelation had a tremendous impact upon the societies, art, and thought of the various peoples with whom it came into contact. But perhaps nowhere is this influence as evident as in the domain of language, the very medium of the revelation. First, the Arabic language itself was radically and irrevocably altered by the manifestation of the Quran.3 Then, as the language of the divine revelation, Quranic Arabic exerted a wide-ranging influence upon the thought and language of speakers of Persian, Turkish, numerous South and South-East Asian languages, and West and East African languages such as Hausa and Swahili.